Polystyrene-template-assisted synthesis of Li3VO4/C/rGO ternary composite with honeycomb-like structure for durable high-rate lithium ion battery anode materials. (1st September 2017) - Yang, Yang; Li, Jiaqi; Huang, Jingxin; Huang, Jianxing; Zeng, Jing; Zhao, Jinbao
Graphical abstract: Highlights: Li3 VO4 /C/rGO ternary composite with honeycomb-like structure is prepared by taking advantage of spray drying method and polystyrene (PS) soft template. Li3 VO4 /C/rGO composite electrode possesses rapid Li + ions intercalation kinetics and good structure integrity. Li3 VO4 /C/rGO composite exhibits outstanding high-rate performance and long cycle-life (the high reversible capacity of 312 mAh g −1 can be maintained after 1000 cycles at 10C). Abstract: Li3 VO4 /C/rGO (HC-LVO/C/G) ternary composite with honeycomb-like structure is successfully prepared through a simple spray drying method with polystyrene (PS) microspheres as soft template. In this characteristic structure, carbon-coated Li3 VO4 nanoparticles are well wrapped by rGO sheets and uniformly distributed within the honeycomb-like micrometer-sized clusters. The double coating layers of amorphous carbon and rGO can avoid the direct exposure of Li3 VO4 nanoparticles to the electrolyte and enhance the electronic conductivity. Meanwhile, the honeycomb-like structure can shorten the diffusion paths of Li + ions and favors the relaxation of the strain/stress during cycling. The resultant HC-LVO/C/G composite exhibits significantly improved high-rate performance and long cycle-life (the high reversible capacity of 312 mAh g −1 can be maintained after 1000 cycles at 10 C) compared with the contrastive Li3 VO4 /C composite synthesized by a typical solid-state reaction method.